La invención del territorio en espacios transimperiales: la región platina a fines del siglo XVIII - Lucía Rodríguez Arrillaga (Centre de Recherches sur les Mondes Américains, 2019)
The aim of the article is to show the processes of territorialization that were taking place in inter-imperial regions where the legal status of the territory, understood as an area of jurisdiction, was going through a permanent process of redefinition. For that purpose, the first part analyses strategies found in two memoirs written by Iberian officials who had experiences in the Río de la Plata region at the end of the 18th century, and attempts to compare and contrast those discourses with the cartographic knowledge that was being produced by members of the delimitation parties by focusing on the dialogue between the two. In the second part, the aim is to show that the use both official make of words related to the land also gives an account of the process of territorialization in progress, and analyses the discursive strategies used by both authors in an effort to turn these lands into territories useful to the "homeland" and "the nation".